2021
DOI: 10.3390/biom11020160
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights into the Potential of Withaferin-A, Withanone and Caffeic Acid Phenethyl Ester for Treatment of Aberrant-EGFR Driven Lung Cancers

Abstract: The anticancer activities of Withaferin-A (Wi-A) and Withanone (Wi-N) from Ashwagandha and Caffeic Acid Phenethyl Ester (CAPE) from honeybee propolis have been well documented. Here, we examined the binding potential of these natural compounds to inhibit the constitutive phosphorylation of epidermal growth factor receptors (EGFRs). Exon 20 insertion mutants of EGFR, which show resistance to various FDA approved drugs and are linked to poor prognosis of lung cancer patients, were the primary focus of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…The potential of CAPE, Wi-A and Wi-N to serve as ATP competitive inhibitors of BRAF WT and BRAF V600E mutant activity was explored in this study. The method used here is similar to our previously published study ( Malik et al., 2021 ). Crystal structure of active conformation of BRAF WT (extracted from BRAF-MEK1 dimer (PDB ID: 4MNE )) and BRAF V600E (PDB ID: 6P7G ) were obtained from Protein Data Bank ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of CAPE, Wi-A and Wi-N to serve as ATP competitive inhibitors of BRAF WT and BRAF V600E mutant activity was explored in this study. The method used here is similar to our previously published study ( Malik et al., 2021 ). Crystal structure of active conformation of BRAF WT (extracted from BRAF-MEK1 dimer (PDB ID: 4MNE )) and BRAF V600E (PDB ID: 6P7G ) were obtained from Protein Data Bank ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed EGFR, ABL and BRAF were among the top hits and indicated that these compounds could serve as a dual inhibitor of EGFR and BRAF like BGB283. In a recently published study, we reported that these molecules might serve as ATP competitive inhibitors against various EGFR mutants, including exon 20 insertion mutations of EGFR ( Malik et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The best-docked poses of the protein–ligand complexes were further taken for molecular dynamics (MD) simulations using Desmond from the Schrodinger suite [ 36 ]. The MD simulation protocol used here has been described in detail in our previous study [ 43 ]. Each of the protein–ligand systems was solvated in TIP3P water model.…”
Section: Methodsmentioning
confidence: 99%
“…The best-docked poses of the protein-ligand complexes were further taken for MD simulations using Desmond from the Schrodinger suite (36). The MD simulation protocol used here has been described in detail in our previous study (43). Each of the protein-ligand systems was solvated in TIP3P water model.…”
Section: Molecular Dynamics (Md) Simulations Of the Docked Systemsmentioning
confidence: 99%